2019
DOI: 10.1016/j.forpol.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

What can we learn from business models in the European forest sector: Exploring the key elements of new business model designs

Abstract: This study represents the first attempt to operationalize a novel methodological approach that couples the expanded business model canvas (BMC) with an analytical evaluation of business model items and incorporates context-intervention-mechanism-outcome logic (CIMO-logic). We applied the designed methodology to analyse ten forest-related business models in eight European countries. This study aims to enhance the understanding of the challenges and opportunities generated by changing forest ownership due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
(43 reference statements)
1
19
0
1
Order By: Relevance
“…The capabilities that FMCs highlight to overcome uncertain conditions are skills in entrepreneurship, market competence/ meeting market requirements, communication skills and the acquisition of support. The results thus confirm the research of Kajanus et al (2019;Lawrence et al 2020;Schaffner et al 2009;Suda et al 2009), who point out the necessity for services. Kieser and Ebers (2014) emphasized that general societal requirements have increased over the last 20 years and organizations must take up and implement these requirements in order to survive.…”
Section: Actors Capabilities and Perceptionssupporting
confidence: 90%
See 1 more Smart Citation
“…The capabilities that FMCs highlight to overcome uncertain conditions are skills in entrepreneurship, market competence/ meeting market requirements, communication skills and the acquisition of support. The results thus confirm the research of Kajanus et al (2019;Lawrence et al 2020;Schaffner et al 2009;Suda et al 2009), who point out the necessity for services. Kieser and Ebers (2014) emphasized that general societal requirements have increased over the last 20 years and organizations must take up and implement these requirements in order to survive.…”
Section: Actors Capabilities and Perceptionssupporting
confidence: 90%
“…increased support for timber selling services or support for management tasks and requirements, under country-specific conditions (Kronholm 2016;Leinert 1996;Moog and Borchert 1999;Ottisch 2001;Petkau 2007Petkau , 2008Schaffner and Suda 1999;Suda et al 2009;Suda and Warkotsch 2002). According to Kajanus et al (2019;Glück et al 2010;Kronholm 2016;Rapp 2000;Sarvašová et al 2014;Selter et al 2009;Schraml 2005Schraml , 2012Petkau 2007), the further development of FMCs is determined by the requirements of private forest owners. These characteristics and preferences of forest owners were analyzed in detail (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It is a template that graphically shows nine interconnected building blocks each of which represents an essential part of an enterprise's business including value proposition, customer segments, customer relationship, customer channels, key partners, key activities, key resources, revenue streams, and cost structure (see Figure 1). Unlike other business models, BMC is distinguished by several strengths including a visual representation of the business components, focus on value creation and delivery, coverage of various dimensions of the business, and easiness to understand by both academics and practitioners (Cabrita et al, 2016;Urban et al, 2018;Kajanus et al, 2019).…”
Section: Business Model Canvasmentioning
confidence: 99%
“…They also argued that the Business Model Canvas (BMC) approach is an adequate tool for incorporating environmentally and socially friendly practices in the original economic-oriented model. Likewise, Kajanus et al (2019) and Ferranti and Jaluzot (2020) reported that BMC has become a common and proper tool for implementing business sustainability through aligning environmental effects, social responsibility, and financial benefits. Accordingly, the current study seeks to develop a holistic business model for sustainable restaurants using the BMC approach.…”
Section: Fig1 Business Model Canvasmentioning
confidence: 99%
“…Dalam memberikan pelayanan kepada tamu, jenis penyajian harus di sesuaikan dengan jenis dan menu yang akan dihidangkan (Davis et al, 2018;Lovelock & Patterson, 2015). Begitu pula metode pembayaran yang harus memenuhi perkembangan seperti dengan pembayaran kontan atau dengan kartu kredit dan yang paling penting bahwa pengelola rumah makan harus bisa menerima keluhan dari tamu demi kelansungan usaha (Kajanus et al, 2018;Kato & Charoenrat, 2018;Kluza & Nalepa, 2017;Liébana-Cabanillas, Herrera, & Guillén, 2016;Snedaker & Rima, 2014;Tucker, 2015;Yip & Bocken, 2018). Selain itu, juga pengelolaan rumah makan harus memperhatikan penyimpanan dan penyajian makanan dan minuman yang memenuhi higiene sanitasi sesuai dengan ketentuan peraturan perundang-undangan, memiliki sertifikat laik higiene sanitasi rumah makan sesuai dengan ketentuan peraturan perundang-undangan, memiliki bahan pembersih untuk pengendalian hama yang baik (Peraturan Menteri Pariwisata dan Ekonomi Kreatif Republik Indonesia Nomor 12 tahun 2012).…”
Section: Pendahuluanunclassified